2009
DOI: 10.1124/mol.109.054833
|View full text |Cite
|
Sign up to set email alerts
|

CYP4F2 Is a Vitamin K1 Oxidase: An Explanation for Altered Warfarin Dose in Carriers of the V433M Variant

Abstract: Genetic polymorphisms in VKORC1 and CYP2C9, genes controlling vitamin K 1 (VK1) epoxide reduction and (S)-warfarin metabolism, respectively, are major contributors to interindividual variability in warfarin dose. The V433M polymorphism (rs2108622) in CYP4F2 has also been associated with warfarin dose and speculatively linked to altered VK1 metabolism. Therefore, the purpose of the present study was to determine the role of CYP4F2 and the V433M polymorphism in the metabolism of VK1 by human liver. In vitro meta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
243
3
7

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 286 publications
(261 citation statements)
references
References 41 publications
8
243
3
7
Order By: Relevance
“…Consistent with this finding is the observation that carriers of the 433Met allele have decreased capacity to metabolize vitamin K [87], and tocopherol [88]. At variance with the results of these studies, the CYP4F2 433Met, but not the 433Val allele, increases the urinary excretion of 20-HETE in a mixed sample of hypertensive and normotensive subjects, suggesting an increased, rather than a decreased, metabolizing capacity [75].…”
Section: Cyp4f2 Hypertension and Cardiovascular Diseasescontrasting
confidence: 47%
“…Consistent with this finding is the observation that carriers of the 433Met allele have decreased capacity to metabolize vitamin K [87], and tocopherol [88]. At variance with the results of these studies, the CYP4F2 433Met, but not the 433Val allele, increases the urinary excretion of 20-HETE in a mixed sample of hypertensive and normotensive subjects, suggesting an increased, rather than a decreased, metabolizing capacity [75].…”
Section: Cyp4f2 Hypertension and Cardiovascular Diseasescontrasting
confidence: 47%
“…9,19,20 CYP4F2 codes for a vitamin K 1 oxidase that causes a decrease in the metabolism of vitamin K 1 . 21 Several studies have shown that carriers of the derived T allele at the non-synonymous SNP rs2108622 require higher warfarin doses than subjects with the ancestral C allele. 22 Studies on European populations have indicated that CYP4F2 rs2108622 may account for an additional 1-7% of observed variation in warfarin dosing.…”
Section: Introductionmentioning
confidence: 99%
“…CYP4F2 is another genetic factor in warfarin processing. CYP4F2 contributes to vitamin K1 oxidation, and some variants could result in reduced enzyme activity [79] . An association between the CYP4F2 variant (rs2108622) and warfarin dose was subsequently confirmed in a meta-analysis involving more than 9000 participants from 30 studies [80] .…”
Section: Warfarinmentioning
confidence: 99%